Особливості оцінки ефективності комплексів електричних теплогенераторів та умови їх впровадження - Derii V.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
The performed studies at the Institute of General Energy of the NAS of Ukraine have revealed the undeniable advantages of electric heat generators (EHG), namely: simplicity of technical decisions (EHG are put on the places of old boilers in existing boiler rooms); ready infrastructure for the transportation and supply of thermal energy; great opportunities for thermal energy storage without additional capital investments; high speed (it is limited only by the requirements to operation of the thermal equipment of district heating system; wide range of the regulation of electric and thermal power; guaranteeing the stability of the united energy system of Ukraine, and low specific capital costs (their average values for Ukraine's energy systems do not exceed € 45–50 / kW of manoeuvring power).It is established that, for the regulation of electric load during the night depression of graphs of electric loads, it is advisable to use mainly electric boilers as electric heat generators, and the contribution of heat pumps should not exceed 15% of the total thermal power of the complexes.When using EHG for daily current load regulation, it is advisable to use heat pumps in the vast majority of cases, and the contribution of electric boilers should not exceed 43% of the total thermal capacity of the complexes. With these ratios of the capacities of electric boilers and heat pumps, the weighted average cost of the thermal energy produced by them will be much lower than the similar over Ukraine as of 2018 (1265.8 UAH / Gcal).The financial possibilities of heat supply companies for the introduction of electric heat generators are analyzed. It is shown that they are currently unable to finance such projects due to the lack of funds. Finally, we develop recommendations on the introduction of EHG at DHS: the increase in the rate of profit of heat supplying enterprises to a level of 10%, the creation of appropriate State Trust Program, the development of regulatory legal framework for their use, and the appropriate technical and software – information tools.